2013
DOI: 10.1002/oby.20211
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of a novel herbal formulation for weight management

Abstract: Objective: To evaluate the efficacy of an herbal blend. Design and Methods: A randomized, double-blind, clinical trial in 60 subjects with body mass index (BMI) between 30 and 40 kg/m 2 . Participants were randomized into two groups receiving either 400 mg herbal capsules or 400 mg placebo capsules twice daily. The herbal blend comprises of extracts from Sphaeranthus indicus and Garcinia mangostana. Participants received a standard diet (2,000 kcal per day) and walked 30 min 5 days per week. Results: After 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 31 publications
2
34
0
Order By: Relevance
“…Sphaeranthus indicus (East India globe thistle) combined with Garcinia mangostana (mangosteen) was examined in two studies (n = 120) conducted by two different research groups in India . Daily dosages were 600 mg of S. indicus and 200 mg of G. mangostana taken over 8 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sphaeranthus indicus (East India globe thistle) combined with Garcinia mangostana (mangosteen) was examined in two studies (n = 120) conducted by two different research groups in India . Daily dosages were 600 mg of S. indicus and 200 mg of G. mangostana taken over 8 and 16 weeks.…”
Section: Resultsmentioning
confidence: 99%
“…One study was rated at low risk of selection bias, attrition bias and other biases; however, had a high risk of detection bias as unblinding occurred prior to data analysis . The other study was rated as having a low risk of attrition bias and reporting bias but could not be assessed for the other criteria because of inadequate reporting . Both studies reported statistically and clinically significant weight differences of −3.7 kg and − 4.0 kg compared to placebo.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical significance was set at ≤0.05. Power calculations, using previously published efficacy data [5, 6], allowed us to conclude that 20 completers per cohort was sufficient to achieve 80 % power to detect outcome differences in weight loss between the groups, assuming a two-sided significance level of 0.05. Thirty subjects per treatment group were calculated to provide more than 90 % power under identical analytical conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier studies reported that an herbal formulation (Meratrim) consisting of extracts of the flower heads from Sphaeranthus indicus and the fruit rinds of Garcinia mangostana demonstrated significant weight loss outcomes in two randomized, double-blind, placebo-controlled clinical studies on obese subjects [5, 6]. An 800 mg daily dose of this supplement resulted in statistically significant reductions in body weight, BMI, waist and hip circumference that exceed those achieved via diet and exercise alone.…”
Section: Introductionmentioning
confidence: 99%
“…Also, some adverse effects such as headache, nausea, gastrointestinal irritation, plus back, leg, ankle, and joint pain were associated with the combination use of S. indicus and G. mangostana (Stern, Peerson, Mishra, Sadasiva Rao, & Rajeswari, 2013).…”
Section: Adverse Effectsmentioning
confidence: 99%